A comparative study of two different techniques of subcutaneous tissue closure in abdominal surgery - Dwivedi, Jyotsna S.; Gupta, Alka S.; Pardeshi, Sachin H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Surgical access to abdomen is required for many operative procedures. The subcutaneous tissue of the anterior abdominal wall can either be sutured or left unsutured with drain in situ. The purpose of this study was to compare the two methods of closure of the subcutaneous tissue and determine the benefit of one over the other. Methods: The study was conducted in a tertiary care centre with sample size of 30 each in study and control group. Patients fulfilling the inclusion criteria were selected and depending on the randomisation the closure of subcutaneous tissue was done either by polyglactin 910, 2-0 or left unsutured with indigenously designed syringe suction drain kept in situ. The patients were followed up till the day of suture removal and further in case of any complications. Results: Total duration taken for the procedure was significantly increased in the study group. There was a significant level of discomfort among the participants due to drain. The rate of surgical site infection, hospital readmission morbidity was significantly higher in the study group. Conclusions: The type of drain studied was indigenously designed where the closed system was not maintained during charging the drain, hence further studies need to be conducted which will compare this with the other closed suction drains to determine the difference in the risk of wound complications.